2023
DOI: 10.1186/s12889-023-15178-w
|View full text |Cite
|
Sign up to set email alerts
|

Action status and willingness to change health-promoting behaviors during the COVID-19 pandemic among elementary school children: a study based on Prochaska’s stages of behavior change theory (TTM)

Abstract: Background & aim: COVID-19 pandemic has significant effects on lifestyle and health-promoting behaviors and adolescence is a very critical period due to the importance of identity formation and individual behaviors. Therefore, the aim of this study was to determine the status of health- promoting behaviors in the sixth grade male students attending elementary schools in Ardabil city based on Prochaska ‘s stages of behavior change (TTM). Materials & methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, some other studies show similar results in the distribution of people in active and passive stages of behavior change. For example, Kamran et al (2023) reported that the distribution of students in the active phases of physical activity and healthy eating during COVID-19 was 38.3% and 45.4%, respectively [ 17 ]. A study in Japan has indicated that more than 60% of people are in the completely inactive stages of pre-contemplation and contemplation about increasing physical activity during the COVID-19 pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some other studies show similar results in the distribution of people in active and passive stages of behavior change. For example, Kamran et al (2023) reported that the distribution of students in the active phases of physical activity and healthy eating during COVID-19 was 38.3% and 45.4%, respectively [ 17 ]. A study in Japan has indicated that more than 60% of people are in the completely inactive stages of pre-contemplation and contemplation about increasing physical activity during the COVID-19 pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kamran et al (2023) showed that the self-efficacy score related to physical activity and healthy nutrition in precontemplators was significantly lower than in the active stages (action and maintenance). This study shows that having more self-efficacy is an effective factor in placing people in higher stages of change and adopting health-promoting behaviors [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation